Le mythe comme détour dans Twelfth Night - Cécile Mauré (Revue LISA)
Being only rarely mentioned in the text, the myth might seem an anecdotal and trivial detail. The study of the myth of Echo and Narcissus in Twelfth Night shows us however that it is a decisive element in the reading and the understanding of the play. The references are numerous and often implicit. The characters themselves alternately play the roles of Echo and Narcissus. The play is structured as if it were a mirror in which the characters endlessly duplicate each other and echo their own words. Shakespeare plays with the different versions of the myth that he often blends with subtlety. For the sake of comedy, he dares to parody and demythologize Ovid’s story. The myth seems to divert our attention from the direction of the text but closer analysis suggests the reverse and invites us to find the meaning of the play which can be seen as a real labyrinth.